CAN A PATIENT-HELD ASSESSMENT TOOL IMPROVE PAIN MANAGEMENT IN PALLIATIVE OUTPATIENTS AT A RURAL KENYAN HOSPITAL?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Besley, Charlie
Abstract : Background: Pain is a frequent and distressing symptom in palliative care patients worldwide. Careful assessment is the first vital step in attempts to relieve this suffering. Assessment tools form a useful adjunct to pain management, but whether they make a difference to the patient themselves is not known. AIC Kijabe Hospital is a busy, rural, 'mission' hospital with an established Palliative Care Team. Aim: The main objective of this study was to investigate whether the use of a pain assessment tool can make a difference to the patient's pain management. Design: A quantitative experimental study methodology was employed, with pre- & post-intervention comparison. In the pre-intervention phase, pain was assessed at study entry and at two weeks, following 'standard' care at home; 49 patients were recruited for this phase. In the intervention phase pain assessments were made at entry, with follow-up assessment after introduction of a patient-held pain assessment tool taken home by each patient; 50 patients were recruited for this phase. Analysis involved a comparison of baseline and two week pain scores between the pre- and post-intervention groups. Results: The results demonstrated that the use of a patient-held pain assessment tool lead to an increase in the number of patients reaching satisfactory pain relief. In the pre-intervention group 30% patients reached satisfactory analgesia, whilst in the intervention group, success rate was 69%. Whilst this was only a pilot study and numbers were small, if we compare follow-up pain scores in the two groups, using a simple chi-squared test analysis, we find a p-value of 0.013, indicating a significant difference. Conclusion: This study has demonstrated that a simple pain assessment tool, when linked to some action, in the hands of palliative care outpatients, may help achieve improved levels of analgesia. This is encouraging, and raises the opportunity for further clinical research in different settings.